Friend vs. Foe: Cognitive and Affective Empathy in Women With Different Hormonal States - Kimmig, Ann-Christin Sophie; Wildgruber, Dirk; Wendel, Sina-Maria Ute; Sundström-Poromaa, Inger; Derntl, Birgit (Frontiers in Neuroscience, 2021)
Empathy is crucial for social functioning as well as social coherence. It can be influenced by modulatory factors such as familiarity and sympathy (i.e. emotional closeness). Furthermore, there are first hints that hormonal status may modulate the affective but not cognitive empathy in women. The aim of this study was to investigate potential modulatory effects of emotional closeness and hormonal status on female cognitive and affective empathy. Three hormonal status groups of women (n=62) were studied: 1) naturally-cycling (NC) women in the early follicular phase (fNC), 2) NC women during periovulatory phase (oNC) and 3) oral contraceptive (OC) users. All women underwent a newly developed empathy task (i.e. Tübinger Empathy Test, TET) presenting textual descriptions of positive and negative emotional scenes relating to three different perspectives (i.e. self vs. friend vs. enemy/disliked person). For both empathy components, empathic responses were higher for the friend compared to the enemy perspective. However, cognitive empathy was less affected by varying emotional closeness towards the target person than affective empathy. Hormonal status modulated only affective empathy. OC users showed significantly less affective empathy towards the enemy compared to the fNC women. Overall, affective empathy seems more sensitive to modulatory effects of emotional closeness and hormonal status than cognitive empathy. Possible implications of this current investigation for future research on empathy and OC use, contraceptive education as well as for other clinical applications are discussed.